CHINESE MIGRANTS IN ITALY: POSITIVE INTEGRATION EXPERIENCE OR A CHALLENGING FACTOR? - K. G. Muratshina; K. M. Tabarintseva-Romanova; Ya. I. Mukhamadiyeva (Vestnik MGIMO-Universiteta)
This paper analyses the situation, caused by the growing labour migration from China to Italy. In the beginning of the paper, the authors give a short outline of multiculturalism policy and its specific features in Italy. In spite of sustainable ethno-religious tolerance of Italian society (conditioned by the historical and geographical factors, such as longterm fragmentation of Italian state, the presence of a large number of ethnic minorities in a rather small area, intensive North-South internal migration), the multiculturalism policy, imposed by the European Union, has not been accustomed in this country. The reasons for it were the growth of unemployment rate, economic crisis, migration crisis, that started after 2008. The latter showed the disrespect, demonstrated by migrants to basic human rights and freedoms, and contempt to European culture and traditions, which induced the increasing discontent among Italian citizens. Then, the paper provides an overview on Italian-Chinese relations and a detailed analysis of problems, related to Chinese migration in Italy. Chinese migrants form a considerable diaspora in this country, living in isolated, almost self-governed communities, claiming for their rights and participating in a variety of criminal activities. The authors define the reasons for the formation of this trend and analyse the way, how the problem is being dealt with.